Navigating the death attitudes and anxiety during COVID-19: Role of dispositional mindfulness and tranquil ego - Satchit Prasun Mandal; Vijyendra Pandey; Raghavendra B. Bonal; Abhishek Sharma; Arora Astha; Viju Rajesh; Proshanto Kr Saha (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Anecdotally, the concept of death consistently evokes profound unease. This study explores the intricate relationship between individuals' attitudes toward death and the associated anxiety, introducing a two-step model that posits dispositional mindfulness and tranquil ego as mediators. MATERIALS AND METHODS: We used a correlational design in this study and assessed 209 Indian adults (111 males and 98 females) who recovered from corona symptoms on self-report measures of attitudes toward death, death anxiety, dispositional mindfulness, and tranquil ego. Bivariate correlational analyses and path analysis were used to analyze the data. RESULTS: Findings revealed that attitudes toward death involving fear, avoidance, approach, and escape acceptance of death correlated positively with death anxiety. Dispositional mindfulness and tranquil ego correlated negatively with death anxiety. Path analyses with percentile bootstrapping supported our hypothesis and showed that dispositional mindfulness and tranquil ego sequentially mediated the relationship. CONCLUSION: These findings indicate that various aspects of attitudes toward death differentially predict death anxiety. Moreover, the relationship between death attitudes and death anxiety is potentially mediated by dispositional mindfulness and a tranquil ego. The findings were discussed in light of existing literature.